Pengaruh Employee Engagement, Budaya Organisasi, dan Work Life Balance terhadap Turnover Intention Guru Secondary Jakarta Islamic School - Achmad Samy Zamzamy (2021)
PENGARUH EMPLOYEE ENGAGEMENT, BUDAYA ORGANISASI, DAN WORK LIFE BALANCE TERHADAP TURNOVER INTENTION GURU SECONDARY JAKARTA ISLAMIC SCHOOL By Achmad Samy Zamzamy Abstract This study is a quantitative study that aims to determine the effect of Employee Engagement, Organizational Culture, and Work Life Balance Turnover Intention. The object of research used in this research is secondary Jakarta Islamic School teacher employees with a total sample of 58 using the saturated sample technique. Data was collected through the distribution of questionnaires. The data analysis technique used is the Partial Least Square (PLS) method with the SmartPLS 3.0 program. The results of this study indicate that Employee Engagement has a significant negative effect on Turnover Intention, Organizational Culture has a significant negative effect on Turnover Intention, while Work Life Balance has no effect on Turnover Intention. Keywords: Employee Engagement, Organizational Culture, Work Life Balance, Turnover Intention